2014
DOI: 10.1016/j.nimb.2013.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Helium mobility in advanced nuclear ceramics

Abstract: I would never have been able to finish my dissertation without the guidance of my laboratory members, help from friends, and support from my family. The contributions of many different people, in their different ways, have made this possible. I would like to extend my appreciation especially to the following.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 130 publications
(169 reference statements)
2
5
0
1
Order By: Relevance
“…The fitted activation energy Q is 0.78 eV, which is in reasonable agreement with the experimental value of 0.77 6 0.08 eV. 10 Obviously, due to the contribution of the change in zero-point vibrational energy ᭝F zp vib at low temperatures, this result is slightly larger than the potential energy barrier of 0.77 eV. The calculated prefactor D 0 (ZrC) is 5.13 Â 10 À11 m 2 s À1 .…”
Section: Diffusion Coefficientsupporting
confidence: 84%
See 2 more Smart Citations
“…The fitted activation energy Q is 0.78 eV, which is in reasonable agreement with the experimental value of 0.77 6 0.08 eV. 10 Obviously, due to the contribution of the change in zero-point vibrational energy ᭝F zp vib at low temperatures, this result is slightly larger than the potential energy barrier of 0.77 eV. The calculated prefactor D 0 (ZrC) is 5.13 Â 10 À11 m 2 s À1 .…”
Section: Diffusion Coefficientsupporting
confidence: 84%
“…34 and 35)], which would enhance the probability of helium trapping, the diffusion coefficient will be reduced to some extent. This prediction is confirmed by Agarwal et al 10 who observed the helium blister close to the surface of ZrC compared to TiC and TiN at 1500 C, which suggests the presence of helium clusters or bubbles. Besides, Yadava 36 clearly validated the existence of over pressurized helium bubbles.…”
Section: Diffusion Coefficientsupporting
confidence: 72%
See 1 more Smart Citation
“…Due to the existence of vacancies or dislocations in the real crystal, the diffusion coefficients will be reduced to a great degree, as investigated in ZrC matrix. 34,35 The formation of helium bubbles would also enhance the probability of helum trapping. To this end, we have made a relevant test to elaborate the effects of the clustering behavior of two helium atoms which can be regarded as the first step to form the helium bubbles.…”
Section: Diffusion Coefficientsmentioning
confidence: 99%
“…From these curves, the extracted kinetic parameters of helium release show that TiN exhibits a very strong helium retention up to 1600°C (less than 20% loss). 41 The 3 He(d, p) NRA characterization has been then transposed to TiC and ZrC compounds. 42 …”
Section: Off-line Characterization By Ibamentioning
confidence: 99%